Pengaruh Partisipasi Penganggaran terhadap Kesenjangan Anggaran dengan Komunikasi sebagai Variabel Moderasi: Studi Perusahaan di Batam - Nabila Shafira Kusnadi; Reni Oktavia; Dewi Sukmasari; Yuliansyah Yuliansyah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aimed at examining the effect of budgeting participation with communication as an intervening variable towards budgetary slack Research Methodology: A quantitative approach was the method used for this analysis. The research was obtained by primary data through the online questionnaire with 255 respondents in Batam’s service companies. The PLS-based structural equation modeling has been used to calculate the statistic of the data. Results: Based on the hypothesis testing result, the result shows that budgeting participation has a significant and positive effect on budgetary slack meaning H1 is accepted. Budgeting participation has a significant and positive effect on communication meaning H2 is accepted. Communication has a significant and positive effect on budgetary slack meaning that H3 is rejected. Communication can mediate budgeting participation on budgetary slack precisely strengthen the budgeting participation towards budgetary slack meaning H4 is accepted Limitations: This study only uses a service company in Batam as a research sample and the communication model used is Kenis (1979) who has modified in research (Ruliana, 2014) Contribution: This study contributes to disseminating information about the influence of budgeting participation as an independent variable on budgetary slack as the dependent variable can be moderated by communication so that the company needs to consider the budgeting process and build a communication climate so that employees can improve their performance.